Rational design of an ion-imprinted polymer for aqueous methylmercury sorption - Mesa, Ruddy L. M. (2020)
Methylmercury (MeHg+) is a mercury species that is very toxic for humans, and its monitoring and sorption from environmental samples of water are a public health concern. In this work, a combination of theory and experiment was used to rationally synthesize an ion-imprinted polymer (IIP) with the aim of the extraction of MeHg+ from samples of water. Interactions among MeHg+ and possible reaction components in the pre-polymerization stage were studied by computational simulation using density functional theory. Accordingly, 2-mercaptobenzimidazole (MBI) and 2-mercaptobenzothiazole (MBT), acrylic acid (AA) and ethanol were predicted as excellent sulfhydryl ligands, a functional monomer and porogenic solvent, respectively. Characterization studies by scanning electron microscopy (SEM) and Brunauer–Emmett–Teller (BET) revealed the obtention of porous materials with specific surface areas of 11 m2 g−1 (IIP–MBI–AA) and 5.3 m2 g−1 (IIP–MBT–AA). Under optimized conditions, the maximum adsorption capacities were 157 µg g−1 (for IIP–MBI–AA) and 457 µg g−1 (for IIP–MBT–AA). The IIP–MBT–AA was selected for further experiments and application, and the selectivity coefficients were MeHg+ /Hg2+ (0.86), MeHg+ /Cd2+ (260), MeHg+ /Pb2+ (288) and MeHg+ /Zn2+ (1510), highlighting the material’s high affinity for MeHg+. The IIP was successfully applied to the sorption of MeHg+ in river and tap water samples at environmentally relevant concentrations.